Residual ligand-functionalized ultrathin Ni(OH)2 via reconstruction for high-rate HO2 − electrosynthesis - Tianyu Zhang; Weibo Wang; Wenxian Liu; Zhengxiao Guo; Junfeng Liu (Nature Communications)
Abstract Reconstruction of metal-organic frameworks often occurs under reaction conditions, thereby impeding true active species identification and hindering mechanism understanding. Herein, we present the mechanistic insight underlying the electrochemical synthesis of deprotonated anion of H2O2 (HO2 −) via 2e− oxygen reduction by ultrathin Ni-benzenedicarboxylic acid (NiBDC), guided by its thickness-dependent performance and pH-induced reconstruction behavior. The real active species are identified as alkaline-reconstructed β-Ni(OH)2 that is chemically coupled with 1,4-benzenedicarboxylic acid residual ligand. The hybrid catalyst is characterized to exhibit an optimized surface electronic structure, which improves the intrinsic activity and selectivity. Operando characterization and theoretical simulations further reveal that the residual ligand functionalization significantly boosts the formation and facilitates the adequate binding of *OOH intermediates. Thus, the ligand-functionalized Ni(OH)2 exhibits high HO2 − selectivity (>90%) in 0.1 M KOH across a broad current density up to 200 mA cm−2. Moreover, high HO2 − production rate of 13.7 mol gcat −1 h−1 with significant accumulation of 2.0 wt.% HO2 − under alkaline conditions is achieved at 200 mA cm−2 over 100 h, suggesting the promising potential for large-scale electrosynthesis of HO2 − in industrial applications.